The hsp70 new functions as a regulator of reproduction both female and male in Ophraella communa - Zhang, Yan; Ma, Weihua; Ma, Chao; Zhang, Qinglu; Tian, Zhenya; Tian, Zhenqi; Chen, Hongsong; Guo, Jianying; Wan, Fanghao; Zhou, Zhongshi (Frontiers in Molecular Biosciences, 2022)
Heat shock proteins (Hsps) function as molecular chaperones that enable organisms to withstand stress and maintain normal life activities. In this study, we identified heat shock protein 70 (encoded by hsp70), which exhibits a higher expression in the mature male testis than in the unmature testis of Ophraella communa. Tissue expression profile revealed that Ochsp70 levels in males were highest in the testis, whereas those in females were highest in the head. Moreover, the expression of Ochsp70 was found to be significantly induced in female bursa copulatrix after mating. Double-stranded RNA dsOchsp70 was injected into males to achieve RNA interference, which significantly decreased the male Ochsp70 expression levels 20 d post-injection, whereas no effect was observed on the Ochsp70 expression level in the females after mating with dsOchsp70-injected males. However, significant downregulation of female fertility was marked simultaneously. Furthermore, knockdown of female Ochsp70 expression also led to a significant reduction in fertility. Finally, comparative transcriptomic analysis identified glucose dehydrogenase and insulin-like growth factor binding protein as putative downstream targets of Ochsp70. Overall, we deduced that Ochsp70 is an indispensable gene and a potential male mating factor in O. communa, which regulates reproduction.